Probabilistic Outcomes Are Valued Less in Expectation, Even Conditional on Their Realization - Paolacci, Gabriele; André, Quentin (Management Science, 2024)
Most theories of decision making under risk assume that payoffs and probabilities are separable. In the context of a lottery, the subjective value of a prospective outcome (the payoff) is assumed to be independent of the likelihood that the outcome will occur (the probability). In violation of this assumption, we present eight experiments showing that people anticipate less utility from uncertain outcomes than from certain outcomes, even conditional on their realization. The devaluation of uncertain outcomes is observed across different measures of utility (willingness to spend money or time; choice between different options), different populations (student and online samples), and different manipulations of uncertainty. We show that this result does not simply reflect a misunderstanding of the instructions or people’s aversion toward a “weird” transaction with unexplained features. We highlight the implications of this phenomenon for empirical investigations of risk preferences and conclude with a discussion of the psychological mechanisms that might drive the devaluation of probabilistic outcomes. This paper was accepted by Yuval Rottenstreich, behavioral economics and decision analysis. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2021.02284 .